HOW IT STARTS AND ENDS: A STUDY OF INDONESIAN STAND-UP COMEDY - Afidah, Lia; Wahyudi, Ribut (Universitas Pendidikan Indonesia, 2014)
This study analyses Indonesian stand-up comedy performances by three comedians, Raditya Dika, Ryan Adryandhi, and Abdel Achrian. Assuming that the stand-up comedy’s opening and ending are the crucial part besides the jokes telling itself, the present study tries to investigate the pattern of their opening and closing compared with the Rutter’s (1997) pattern known in British stand-up comedian. Basically, stand-up comedy is similar with common conversation since it involves two participants, the comedian and the audience. The 153 lines of conversation are extracted from the videos are randomly collected from YouTube video site from 2011 to 2013. Conversation analysis on humor is the most appropriate framework to be used in the present study. As the result, the opening and closing indicate some similarities with the Rutter’s pattern.